2004
DOI: 10.1063/1.1779972
|View full text |Cite
|
Sign up to set email alerts
|

Probing intrinsic transport properties of single metal nanowires: Direct-write contact formation using a focused ion beam

Abstract: Access to the full text of the published version may require a subscription. Probing intrinsic transport properties of single metal nanowires: Direct-write contact formation using a focused ion beam The transport characteristics of 70-nm-diameter platinum nanowires (NWs), fabricated using a pore-templated electrodeposition process and individually contacted using a focused ion beam (FIB) method, are reported. This approach yields nanowire devices with low contact resistances ͑ϳ400 ⍀͒ and linear current-voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
76
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 35 publications
8
76
2
1
Order By: Relevance
“…The NWs of Pt, Au, and Cu were shown to have resistivities as high as 3, 7, 26 times of the corresponding bulk metal, respectively. [10,11,25] Twoand four-probe transport measurements on Au and Pt NWs made by axial solution growth [26][27][28] displayed resistivities from 10 [28] to as high as 100 times [26,27] higher than the bulk. These observations raise several basic questions related to nanoscale interconnects.…”
mentioning
confidence: 98%
“…The NWs of Pt, Au, and Cu were shown to have resistivities as high as 3, 7, 26 times of the corresponding bulk metal, respectively. [10,11,25] Twoand four-probe transport measurements on Au and Pt NWs made by axial solution growth [26][27][28] displayed resistivities from 10 [28] to as high as 100 times [26,27] higher than the bulk. These observations raise several basic questions related to nanoscale interconnects.…”
mentioning
confidence: 98%
“…This is very low for nanowire devices. [27] Control electrical measurements were also undertaken in the absence of nanowires, yielding very low currents and high resistances (~10 GΩ), typical of an open circuit. This confirmed that the observed Ohmic behaviour of the nanowire electrodes was exclusively due to the nanowire electrodes and associated on-chip metallisation interconnections with no contribution from the underlying silicon substrate.…”
Section: Nanowire Electrical Characterisationmentioning
confidence: 99%
“…[8] Recently, direct writing techniques using focused ion beams (FIBs) have been used to form interconnects to individual nanowires. [9][10][11][12][13] To do this, an organoplatinum precursor gas flow was directed at the surface of the sample while the target region was irradiated with an energetic particle beam, which decomposed the gas and deposited Pt over the irradiated region. Decomposition of the precursor and Pt deposition can be achieved using focused beams of ions (IBID-Pt, where IBID = ion-beaminduced deposition) [9,10,12,13] or electrons (EBID-Pt, where EBID = electron-beam-induced deposition).…”
mentioning
confidence: 99%